Karl Leonhard Reinhold y Edmund Husserl. Two Conceptions of the Phenomenology - Vargas Bejarano, Julio César (Estudios de Filosofía, 2016)
A century before Husserl, in order to complete the system of Kantian philosophy, motivated by the ideals of the Enlightenment and its theological and religious questions, Reinhold designed the program to raise “philosophy to a rigorous science.” For this he developed a discipline whose aim is to access -reflexively- to the elementary principles of consciousness, the faculty of representation. This discipline must be validated phenomenologically. Although at first glance the phenomenology of Reinhold (even in its later 1802 version), has several aspects in common with that of Husserl, there are differences of principle. The comparison between these conceptions of phenomenology, the explicit expression of their convergences and differences, allows to clarify, first, in what sense a conception of ‘phenomenon’ restricted to the manifestation is too narrow; second, what are the limits of a theory of self-consciousness based on reflection, according to an “optical” model. Thus, it is shown that, despite its limitations and weaknesses, the phenomenology of Reinhold keeps shedding lights on philosophical inquiry.